Mutations in γ-aminobutyric acid (GABA) transaminase genes in plants or Pseudomonas syringae reduce bacterial virulence. - Park, D; Mirabella, R; Bronstein, P; Preston, G; Haring, M; Lim, C; Collmer, A; Schuurink, R (2010)
Pseudomonas syringae pv. tomato DC3000 is a bacterial pathogen of Arabidopsis and tomato that grows in the apoplast. The non-protein amino acid γ-amino butyric acid (GABA) is produced by Arabidopsis and tomato and is the most abundant amino acid in the apoplastic fluid of tomato. The DC3000 genome harbors three genes annotated as gabT GABA transaminases. A DC3000 mutant lacking all three gabT genes was constructed and found to be unable to utilize GABA as a sole carbon and nitrogen source. In complete minimal media supplemented with GABA, the mutant grew less well than wild-type DC3000 and showed strongly reduced expression of hrpL and avrPto, which encode an alternative sigma factor and effector, respectively, associated with the type III secretion system. The growth of the gabT triple mutant was weakly reduced in Arabidopsis ecotype Landberg erecta (Ler) and strongly reduced in the Ler pop2-1 GABA transaminase-deficient mutant that accumulates higher levels of GABA. Much of the ability to grow on GABA-amended minimal media or in Arabidopsis pop2-1 leaves could be restored to the gabT triple mutant by expression in trans of just gabT2. The ability of DC3000 to elicit the hypersensitive response (HR) in tobacco leaves is dependent upon deployment of the type III secretion system, and the gabT triple mutant was less able than wild-type DC3000 to elicit this HR when bacteria were infiltrated along with GABA at levels of 1 mm or more. GABA may have multiple effects on P. syringae-plant interactions, with elevated levels increasing disease resistance.